KESESUAIAN ANTARA PELAKSANAAN PEMELIHARAAN FASILITAS PADA TERMINAL TERPADU PULO GEBANG SESUAI DENGAN SOP PERATURAN MENTERI PU NO. 24 PRT/M/2008 - Lintang Bagus Perdana; Lenggogeni Lenggogeni; Prihantono Pihantono (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2020)
This research purpose is to find out the management and maintenance curing of Pulogebang Integrated Bus Terminal already match according to PU Minister Regulations No. 24 PRT/M/2008 SOP. Corresponding to the observation that already do indicates that maintenance and curing assignment in Pulogebang Integrated Bus Terminal are far from optimum. It is because some factor that is SOP (Standart Operational Procedure) that hasn’t been match according to PU Minister Regulations No. 24 PRT/M/2008, bureaucracy system in the government, feebleness in control system and facility that not appropriate yet according to Ministry of Transportation Regulations No. 132 2015.